Pelayanan Publik: Kajian Pendekatan menurut Perspektif Islam - Jailani Jailani (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2013)
Public service is all service activities undertaken by public service providers as addressing the needs of service recipients as well as the implementation of the provisions of the legislation. Public can also be interpreted as many people or too general. The principle of transparency means a unit of public services should be open, easy and accessible to all who need and provided adequately and easy to understand. The principle of accountability; Conditional; Participatory; Equal rights; Simplicity; Clarity; Certainty time; accuracy; Security; responsibility; Completeness means and Keprasaranaan; Then access; discipline, politeness and friendliness, as well as comfort. Service approach is Islam that is the approach teleology and deontology approach "approach of teleology that is contrary to the understanding that what is good and what is bad or what should be done by public officials based on the value of the benefit to be obtained or generated, that is good or bad views of konsekkuensi decisions or actions taken are comprehensively. Deontological approach is based on the moral principles that should ditegakkkan because of the truth that was in him and not associated with the effect or consequences of decisions or actions that have been done .. This approach is based on values and moral belandaskan binding. Emperis in the world, enter into the moral values of public service management is not an easy thing, because it deals with an attempt to make changes in the mindset of bureaucrats who have internalized as bureaucratic officials.